2011
DOI: 10.1016/j.ejmech.2011.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and anticonvulsant properties of 1-(amino-N-arylmethanethio)-3-(1-substituted benzyl-2, 3-dioxoindolin-5-yl) urea derivatives

Abstract: Various 1-(amino-N-arylmethanethio)-3-(1-substituted benzyl-2, 3-dioxoindolin-5-yl) urea (5a-p) were designed keeping in view the structural requirements suggested in the pharmacophore model for anticonvulsant activity. Their in vivo anticonvulsant screenings were performed by two most adopted seizure models, maximal electroshock seizure (MES) and subcutaneous pentylenetetrazole (scPTZ). Compound 5f was found active in MES screening while compounds 5h, 5i, 5k and 5l showed significant anticonvulsant activity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…The results revealed that compound 31f was found active in MES screening while compounds 31h, 351, 31k and 31l showed significant anticonvulsant activity in both the screenings and were devoid of any neurotoxicity. Compound 31h and 31i showed marked protection at 300 mg/kg against MES and scPTZ screening 29 .…”
Section: Anticonvulsant Activitymentioning
confidence: 96%
“…The results revealed that compound 31f was found active in MES screening while compounds 31h, 351, 31k and 31l showed significant anticonvulsant activity in both the screenings and were devoid of any neurotoxicity. Compound 31h and 31i showed marked protection at 300 mg/kg against MES and scPTZ screening 29 .…”
Section: Anticonvulsant Activitymentioning
confidence: 96%
“…Compounds 2, 3 and N-benzylisatins were prepared by reported [24][25][26]32) procedures and their physical and spectral data are in accordance with the earlier reports. [24][25][26][32][33][34] General Method for Synthesis of Isatin Substituted Ciprofloxacin Derivatives (4-6) To a mixture of appropriate N-benzylisatin (1 mmol) and ciprofloxacin acid hydrazide…”
Section: Experimental Molecular Property Prediction Molsoft Molinspimentioning
confidence: 99%
“…According to the reported literature, the 5-nitroisatin 2 was prepared [33]. In 500 ml round-bottomed flask (RBF), 0.33 mol of isatin (48.5 g) was added slowly to a mixture of 0.5 mol conc.…”
Section: Preparation Of 5-nitroisatin (2)mentioning
confidence: 99%